Analisis pelaksanaan program Pelayanan Kesehatan Peduli Remaja (PKPR) pada masa pandemi COVID-19 di Puskesmas Kota Metro - Septiani, Ranny; Anggraini, Yetti; Martini, Martini; Putriana, Yeyen (MEDIA ILMU KESEHATAN, 2023)
Background: Adolescent Care Health Service (PKPR) is a health service program aimed at adolescents at the Health Center, to create "healthy youth". committed to running the program, lack of fund allocation, lack of infrastructure that can support the implementation of PKPR according to national standards, and has not been recorded and evaluated according to standards so that the most prominent problems are not found to be followed up.Objective: This study aims to analyze the implementation of the program at the Metro City Health CenterMethod: Descriptive research with a quantitative approach with a cross-sectional design to find out the description of the implementation of the program at the Health Center. The population of this study was the head of the Health Center as the person in charge of the program, implementing officers, support officers, and assisted youth in the working area of Metro City, totaling 40 people. The instrument used is the published National Adolescent Health Service Standards questionnaire.Results: The level of compliance is still low, namely youth standards, networking and health management.Conclusion: Screening youth problems as a promotive and preventive effort needs to be underlined, there must be an increase in services that reach all youth.